1997
DOI: 10.1136/bjo.81.3.180
|View full text |Cite
|
Sign up to set email alerts
|

Retinal detachment in AIDS: long term results after repair with silicone oil

Abstract: Aims-To study the long term results of vitrectomy and silicone oil injection in AIDS patients with retinal detachment due to viral retinitis. Methods-A consecutive series of 83 eyes in 75 AIDS patients who were treated with vitrectomy and silicone oil for retinal detachment due to viral retinitis was studied prospectively and followed until the last patient in the series had died. Results-Median postoperative survival was 6 months, but 20% of patients survived 12 months or more. Whereas best corrected visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In addition, silicone oil is usually employed in the first surgical procedure in patients unable to position for gases, with need to air travel immediately after surgery [82] or suffering from AIDS and related retinal complications [83,84].…”
Section: Silicone-based Oilsmentioning
confidence: 99%
“…In addition, silicone oil is usually employed in the first surgical procedure in patients unable to position for gases, with need to air travel immediately after surgery [82] or suffering from AIDS and related retinal complications [83,84].…”
Section: Silicone-based Oilsmentioning
confidence: 99%
“…Arch Ophthalmol. 2005;123:473-478 S ILICONE OIL WAS FIRST REported for the treatment of retinal detachment in 1962 1 and has been used increasingly as a retinal tamponade in the management of complex retinal detachments associated with cytomegalovirus necrotizing retinitis, [2][3][4][5][6][7][8][9][10][11] proliferative diabetic retinopathy, [12][13][14][15][16][17][18] giant retinal tears, [19][20][21][22][23][24][25][26][27][28] proliferative vitreoretinopathy, [29][30][31][32][33][34][35][36][37] and ocular trauma. [38][39][40][41][42][43][44][45] The National Eye Institute Silicone Study demonstrated the superiority of 1000-centistoke silicone oil compared with sulfur hexafluoride, and its comparability with perfluoropropane, for ...…”
mentioning
confidence: 99%
“…16.32 Despite reattachment of the retina in this patient with ARN, there is CMO of the macula Fig. This is characterised by posterior segment in fl ammation which causes secondary complications such as cystoid macular oedema (Irvine et al 1997 ) , vitreomacular traction (Canzano et al 1998 ) , vitreous haemorrhage from retinal neovascularisation (Wright et al 2003 ) , and even activation of previously quiescent infections of the retina such as mycobacteria (Zamir et al 2002 ) . This is characterised by posterior segment in fl ammation which causes secondary complications such as cystoid macular oedema (Irvine et al 1997 ) , vitreomacular traction (Canzano et al 1998 ) , vitreous haemorrhage from retinal neovascularisation (Wright et al 2003 ) , and even activation of previously quiescent infections of the retina such as mycobacteria (Zamir et al 2002 ) .…”
Section: Clinical Featuresmentioning
confidence: 95%
“…This has led to a massive reduction in the numbers of new cases of retinitis which may only occur when there is failure of or resistance to HAART (Uphold et al 1998 ;Mitchell et al 1999 ;Mocroft et al 2000 ;Jalali et al 2000 ) . Prior to HAART, this was linked to early mortality at approximately 6 months (Dugel et al 1991 ;Irvine et al 1997 ) . Prior to HAART, this was linked to early mortality at approximately 6 months (Dugel et al 1991 ;Irvine et al 1997 ) .…”
Section: Clinical Featuresmentioning
confidence: 99%